1991
DOI: 10.1063/1.349828
|View full text |Cite
|
Sign up to set email alerts
|

Electro-optic response of polymer dispersed liquid-crystal films

Abstract: The electro-optic response of polymer dispersed liquid-crystal (PDLC) films is reported as a function of frequency and amplitude of the applied voltage and size of the LC droplets. We found that the threshold voltage is minimum and sharpest at frequencies near a few kHz. Visual and optical response studies show that there are two types of PDLC films; type I, which exhibit large partial optical memory, and type II, which quickly regain their original levels of transmittance after switching off relatively small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(41 citation statements)
references
References 7 publications
1
39
0
1
Order By: Relevance
“…Fuh et al investigated PDLC lms based on E7 / EPO305 and found that a plot of transmission polymer refractive indices, etc. [11][12][13][14][15]. Interfacial eOE ects are also important due to the increased surface-to-volum e as a function of temperature showed broad peaks [18].…”
Section: Introductionmentioning
confidence: 99%
“…Fuh et al investigated PDLC lms based on E7 / EPO305 and found that a plot of transmission polymer refractive indices, etc. [11][12][13][14][15]. Interfacial eOE ects are also important due to the increased surface-to-volum e as a function of temperature showed broad peaks [18].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of decreased droplet size, rise time slightly decreases with increasing content of surfactant due to the decreased anchoring energy. Decay time significantly increases with increasing voltage due to the greater distortion of the director and in turn a greater restoration energy [38] under high applied field. It was also found that decay time decreases with increasing content of surfactant, mainly due to the small droplet size.…”
Section: Electro-optical Propertiesmentioning
confidence: 98%
“…However, the interaction between the electric field and the liquid crystal competes with the interfacial energy between the liquid crystal and the polymer wall of the droplet [22,23] . Decreasing R causes an increase in the surface anchoring energy of the LC, thus more voltage is needed to switch the LC.…”
Section: Electro-optic Characteristicsmentioning
confidence: 98%